Delirious Mania: Can We Get Away with This Concept? A Case Report and Review of the Literature. (12th November 2012) - Bipeta, Rajshekhar; Khan, Majeed A.
Abstract : Background . Delirious mania (DM) as a clinical entity is well described, yet is often unrecognized in clinical practice. While most often misdiagnosed as acute psychotic episodes of organic delirium, these patients meet the criteria for mania with attendant delirium and pose therapeutic challenges. In addition to the case presentation, this paper also discusses the available literature on DM. Case Presentation . A 29-year-old man with DM was treated with a combination of electroconvulsive therapy (ECT), divalproex 2000 mg/day, loxapine 100 mg/day, and lorazepam 4 mg/day. He demonstrated clinically significant improvement by day 10, which persisted through the twelve-month follow-up period. Conclusions . DM is a severe psychiatric syndrome which should be accurately diagnosed. Patients with DM should be treated aggressively, especially with ECT. Lack of recognition of DM can lead to serious morbidity or fatal outcomes. Though the concept of DM is well established, recent psychiatric literature does not make a mention of this life threatening yet treatable condition. We propose that there is a dire need to keep this concept alive.